2012
DOI: 10.4238/2012.march.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between Gly82Ser, 1704G/T and 2184A/G of RAGE gene polymorphisms and retinopathy susceptibility in Malaysian diabetic patients

Abstract: ABSTRACT. Diabetic retinopathy is the most common diabetic eye disease, occurring in about 60% of type 2 diabetic patients. Other than known clinical risk factors, the influence of genes has been suggested as part of the development of diabetic retinopathy. We investigated the association of Gly82Ser, 1704G/T and 2184A/G polymorphisms in the RAGE gene with retinopathy in type 2 diabetic patients in Malaysia. Ninety-eight unrelated retinopathy patients and 185 unrelated healthy controls from all over Malaysia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 87 publications
0
14
2
1
Order By: Relevance
“… 40 Alternatively, a series of 758 North Indian patients reported a significant association between the homozygous Ser82 genotype of the Gly82Ser polymorphism with DR in type 2 diabetes ( P <0.033). 41 However, one series of 283 Malaysian patients with type 2 diabetes 42 and one meta-analysis of over 1,000 patients from 29 studies from the US, Europe, and Asia 43 reported no associations between RAGE polymorphisms and DR.…”
Section: Well-studied Candidate Genesmentioning
confidence: 99%
“… 40 Alternatively, a series of 758 North Indian patients reported a significant association between the homozygous Ser82 genotype of the Gly82Ser polymorphism with DR in type 2 diabetes ( P <0.033). 41 However, one series of 283 Malaysian patients with type 2 diabetes 42 and one meta-analysis of over 1,000 patients from 29 studies from the US, Europe, and Asia 43 reported no associations between RAGE polymorphisms and DR.…”
Section: Well-studied Candidate Genesmentioning
confidence: 99%
“… 24 Many studies have investigated the association between various SNPs in the AGER gene with DR, but the results of these association studies have been inconsistent or even directly conflicting. For example, some studies suggested that the AGER polymorphisms −429 T/C, −374 T/A, Gly82Ser, 1704G/T, and 2245G/A are associated with DR, 16 , 25 30 while other studies, including a previous study from our group, did not support a significant association between these polymorphisms and DR. 31 37 These studies also suggested that these AGER gene polymorphisms have different distributions in different ethnic populations, which may be associated with the different contributions of these mutations against different ethnic backgrounds. 35 , 36 A significant association between the Gly82Ser polymorphism in the AGER gene with DR has been reported in Asian Indians 38 , 39 and Asian Chinese 29 with T2DM.…”
Section: Discussionmentioning
confidence: 92%
“…The results of this present study were similar to those previously reported. 31 , 32 , 40 Two important differences exist between this present study and a previous study that also reported on a Chinese population: 40 (i) this present study exclusively assessed a Han Chinese population, while the previous study evaluated a general Chinese population; and (ii) the present study used polymerase chain reaction–restriction fragment-length polymorphism, while the previous study utilized chip-based matrix-assisted laser desorption ionization time-of-flight mass spectrometry for genotypic analysis. Furthermore, another study reported that the 2184A/G polymorphism in the AGER gene was associated with diabetes-associated microvascular dermatoses in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…T − 553 Ac. T−834A42CaucasianAT genotype could be risk factor for PDR during T2DM[50]IGF-1Insulin-like growth factor 1Stimulation of cell growth and proliferation, inhibition of apoptosis(CA)n42Southern Indian18-repeat of (CA) increases risk of DR[51]EPOErythropoietinControl of erythropoiesis, stimulation of proliferation, migration and angiogenesis in hypoxic cellsrs1617640, rs507392, rs55123871 and 2Multi-ethnic, European American, AustralianTTA allele associated with PDR in European American, meta-analysis hasn´t found significant association; GCC haplotype associated with DR in Australian[15, 52, 53]RAGEAdvanced glycosylation end product-specific receptorActivation of pro-inflammatory genesrs1800624 (c. T-374A)62Indian, Chinese, African-Brazilian, Caucasian - ScandinavianInconsistent finding and weak association, may be interacting with glycosylated hemoglobin[15, 5456]rs1800625 (c. T-429C)62Caucasian, Indians, DanishInconsistent finding and weak association, functional studies show differences in polymorphic receptor activity[5560]rs2070600 (p. G82S)62Caucasian, Indian, Chinese, MalaysianAssociated with DR, no association in Malaysian[15, 58, 61]ACE IAngiotensin-I converting enzymeComponent of the renin-angiotensin system—activation of angiotensin IIrs4646994 (c. G2350A)-INS/DEL at intron 16171 and 2Caucasian - Slovene, Danish; J...…”
Section: Polyol Pathway and Its Role In Drmentioning
confidence: 99%